Association Between Cervical Screening and Prevention of Invasive Cervical Cancer in Ontario. Issue 1 (January 2015) - Vicus, Danielle; Sutradhar, Rinku; Lu, Yan; Kupets, Rachel; Paszat, Lawrence
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to estimate the effect of cervical screening in the prevention of invasive cervical cancer among age groups, using a population-based case-control study in the province of Ontario, Canada. Methods Exposure was defined as cervical cytology history greater than 3 months before the diagnosis date of cervical cancer (index date). Cases were women who were diagnosed with cervical cancer between January 1, 1998, and December 31, 2008. Controls were women without a diagnosis of cervical cancer on, or before, December 31, 2008. Two controls were matched to each case on year of birth and income quintile, as of the index date. Conditional logistic regression was used to estimate the odds ratio for having been screened among those with cervical cancer. Results Cervical cancer screening performed between 3 and 36 months before the index date was protective against invasive cervical cancer in women aged 40 through 69 years. In women younger than 40 years, cervical cancer screening performed 3 to 36 months before the index date was not protective. Conclusions Cervical screening is associated with a reduced risk for invasive cervical cancer among women older than 40 years. Cervical cancer resources should be focused on maximizing the risk reduction.